The SAMI Galaxy Survey: the link between [α/Fe] and kinematic morphology. Issue 4 (3rd May 2022) - Watson, Peter J; Davies, Roger L; van de Sande, Jesse; Brough, Sarah; Croom, Scott M; D'Eugenio, Francesco; Glazebrook, Karl; Groves, Brent; López-Sánchez, Ángel R; Scott, Nicholas; Vaughan, Sam P; Walcher, C Jakob; et al.
ABSTRACT: We explore a sample of 1492 galaxies with measurements of the mean stellar population properties and the spin parameter proxy, λ _R_e, drawn from the SAMI Galaxy Survey. We fit a global [α /Fe] –σ relation, finding that [α /Fe]=(0.395± 0.010)log_10(σ)-(0.627± 0.002) . We observe an anti-correlation between the residuals Δ [α /Fe] and the inclination-corrected λ _ R_e^ eo, which can be expressed as Δ [α /Fe]=(-0.057± 0.008)λ _ R_e^ eo+(0.020± 0.003) . The anti-correlation appears to be driven by star-forming galaxies, with a gradient of Δ [α /Fe](-0.121± 0.015)λ _ R_e^ eo, although a weak relationship persists for the subsample of galaxies for which star formation has been quenched. We take this to be confirmation that disc-dominated galaxies have an extended duration of star formation. At a reference velocity dispersion of 200 km s −1, we estimate an increase in half-mass formation time from ∼0.5 Gyr to ∼1.2 Gyr from low- to high-λ _ R_e^ eo galaxies. Slow rotators do not appear to fit these trends. Their residual α-enhancement is indistinguishable from other galaxies with λ _ R_e^ eo0.4, despite being both larger and more massive. This result shows that galaxies with λ _ R_e^ eo0.4 experience a similar range of star formation histories, despite their different physical structure and angular momentum.